Optimization of Temperature to Bacteriocin by Lactobacillus acidophilus Against Methicillin-Resistant Staphylococcus aureus - Putri, Cut Laras Dwi Hendia; Suryani, Lilis (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2025)
Introduction: Methicilin resistant Staphylococcus aureus (MRSA) is a pathogenic bacterium that has evolved resistance to antibiotics. MRSA is resistant to the antibiotics methisillin, cephalosporin, and betalaktam. MRSA causes many health problems ranging from lung damage to septicemia. The prevalence of MRSA infections in the world reached 14.69%. Lactobacillus acidophilus produces an antimicrobial substance bacteriosine. These bacteriosins have bactericidal and bacteriostatic activity. Purpose: The study aims to recognize the influence of temperature on the activity of bacteriosins produced by L.acidophilus against MRSA. Methode: This research used a quasi-experimental method. L.acidophilus reproduced on liquid MRS media for 48 hours. Bacteriosine is obtained by centrifying a MRS broth containing bacteria at a speed of 6000 rpm for 40 minutes. The fluid was tested for its antibacterial effects on MRSA bacteria using Kirby Bauer's method. Bacteriosine is given at different temperatures that is; 40, 60, 80, dan 100 oC. The diameter of the formed barrier zone is measured in millimeters. Data analysis with ANOVA method. Finding: Bacteriosine activity produced by Lactobacilus acidophilus against MRSA shows an average inhibition zone diameter of 5.25 mm. The optimum broadest spectrum of antibacterial activity at temperature 60 oC. Conclusion: This research shows that temperature does not affect the antibacterial activity of bacteriosin produced by L.acidophilus against MRSA. Originality/Implication: The results of this study prove that temperature treatment with various variations does not affect the ability of the bacteriosine produced by L.acidophilus to inhibit/kill MRSA.